Energy asset stranding in resource-rich developing countries and the just transition - A framework to push research frontiers - Hoffart, Franziska M.; Holz, Franziska (Frontiers in Environmental Economics, 2024)
Climate policy will inevitably lead to the stranding of fossil energy assets such as production and transport assets for coal, oil, and natural gas. Resource-rich developing countries are particularly affected, as they have a higher risk of asset stranding due to strong fossil dependencies and wider societal consequences beyond revenue disruption. However, there is only little academic and political awareness of the challenge to manage the asset stranding in these countries, as research on transition risk like asset stranding is still in its infancy. We provide a research framework to identify wider societal consequences of fossil asset stranding. We apply it to a case study of Nigeria. Analyzing different policy measures, we argue that compensation payments come with implementation challenges. Instead of one policy alone to address asset stranding, a problem-oriented mix of policies is needed. Renewable hydrogen and just energy transition partnerships can be a contribution to economic development and SDGs. However, they can only unfold their potential if fair benefit sharing and an improvement to the typical institutional problems in resource-rich countries, such as the lack of rule of law, are achieved. We conclude with presenting a future research agenda for the global community and academia.